Hubungan Teknologi Informasi dan Formulasi Strategi Kompetitif Serta Dampaknya Terhadap Kinerja Organisasional: Kerangka Konseptual - Agustinus Dedy Handrimurtjahjo (Bina Nusantara University, 2014)
The relationship between IT and firm performance is a crucial research issue that symbolizes the value of information systems research. Many studies have attempted to understand the role of IT in organizational performance, and more researchers are paying attention to the notion of IT capabilities, including their potential to transform IT resources into business value. Meanwhile, the other study identified and investigated the three building blocks of IT deployment capabilities: strategic IT flexibility, business–IT partnership, and business–IT alignment. Using the resource-based view, the study propose a framework to explain the relationship between IT deployment capabilities and competitive advantage. This paper aims to find relationship between IT and Competitive Strategies and their impact on Organizational Performance.